2007
DOI: 10.1007/s10457-007-9088-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation of pomelo (Citrus grandis (L.) Osbeck) in Nepal and participatory selection of strains for further improvement

Abstract: A farmers' participatory survey was carried out in the mid-hill and plain (Terai) regions of Nepal to assess the diversity, consumers' preference for fruit quality and potential for selection of elite pomelo clones. A wide variation of morphological characters of tree, fruit, leaf and seed was identified from information gathered and from laboratory analysis. Multivariate analysis of the data produced five discrete groups, which were represented by plants from different agro-ecological regions and soil types. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 2 publications
(2 reference statements)
2
9
0
1
Order By: Relevance
“…Citrus fruits (Rutaceae) are popularly grown all over the world and sub-divided into 78 species, with their distinctive and varied flavors (Texeira et al, 2005;Dkwi & Emenike, 2006). Fruit characteristics are one of the important parameters used for the selection of best genotypes for further propagations (Paudyal & Haq, 2008), and total soluble solid is an important economic index, especially with frozen concentrates (Rouse, 2000). Citrus fruits are mostly considered as acid fruits, since their soluble solids are composed mainly of organic acids and sugars (Kelebek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Citrus fruits (Rutaceae) are popularly grown all over the world and sub-divided into 78 species, with their distinctive and varied flavors (Texeira et al, 2005;Dkwi & Emenike, 2006). Fruit characteristics are one of the important parameters used for the selection of best genotypes for further propagations (Paudyal & Haq, 2008), and total soluble solid is an important economic index, especially with frozen concentrates (Rouse, 2000). Citrus fruits are mostly considered as acid fruits, since their soluble solids are composed mainly of organic acids and sugars (Kelebek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Elite genotypes of citrus fruit can be selected through the assessment of tree mor-phological characters and consumer's preference. Farmers are highly preferred the quality rather than size and yield of the fruits [7]. Consumers prefer the fruit quality of acid lime is round, thin skinned, yellow colour; juicy and medium size 35 -50 g [4].…”
Section: Introductionmentioning
confidence: 99%
“…The soil texture and soil drainage could correlate with the soil fertility condition, which then could affect the size of the plant. Other study on pomelo (Citrus grandis) in Nepal found that yield related characters, such as fruit weight had positively correlated with tree size and soil fertility level, but none of these factors were correlated with fruit quality, such as percent of pulp and pulp SSC (Paudyal & Haq, 2008) It could be seen at Table 7 that there was significant correlation among the variable of B. dulcis trees and fruits in West Java. Significant positive correlations were found between (1) Canopy diameter and trunk width; (2) Maximum fruit width and fruit weight, pulp thickness, peel color, peel thickness, pulp soluble solid content (SSC), seed length, seed width, seed weight; (3) Maximum fruit length and seed weight per fruit; (4) Fruit weight and peel color, peel thickness, pulp SSC, seed length, seed width, seed weight; (5) Pulp thickness and peel weight, pulp SSC, seed width, seed weight; (6) Easiness to peel and peel color; (7) Peel color and peel thickness; (8) Peel thickness and pulp SSC, seed length, seed width, seed weight, pulp portion; (9) Pulp color and seed weight, pulp weight; (10) Pulp SSC and seed width; (11) Maximum seed length and maximum seed width, seed weight; (12) Maximum seed width and seed weight.…”
Section: Correlations Among Habitat Plant and Fruit Variablesmentioning
confidence: 83%
“…Group 5 were characterized by big and more heavy fruit, thick and more heavy fruit peel, fruit pulp color white/transparent, big seed and high portion of fruit pulp, whereas group 6 were characterized by light fruit, sour taste, small seed, color of fruit pulp reddish or purple (Table 4). Another study on the variation of pomelo (Citrus grandis) in Nepal found that from the multivariate analysis of the data produced five discrete groups, which differed significantly in fruit shape and size, pulp, juice, total soluble solids and acid content, seed number, leaf shape and size (Paudyal & Haq, 2008 …”
Section: Clustering Of Baccaurea Dulcis Variation In West Javamentioning
confidence: 99%